Association analysis of germline mutations in CHEK2, PALB2, NBN and RECQL with the risk of ductal carcinoma in situ in Polish women - Feszak, Sylwia; Kluźniak, Wojciech; Feszak, Igor; Chady, Magdalena; Wokołorczyk, Dominika; Stempa, Klaudia; Rudnicka, Helena; Gliniewicz, Katarzyna; Jakubowska, Anna; Lener, Marcin; Czepukowicz, Maciej; Huzarski, Tomasz; et al. (Hereditary cancer in clinical practice, 2025)
Background The genetic background of ductal carcinoma in situ (DCIS) has not been well explored. Previously, we reported that Polish founder mutations of BRCA1/2 confer susceptibility to DCIS. The aim of our study was to investigate the role of CHEK2 , PALB2 , NBN and RECQL mutations in the ethology of DCIS. Methods We studied 564 Polish women with DCIS for eight Polish founder alleles, including four in CHEK2 (c.1100delC, c.444 + 1G > A, del5395 and c.470T > C), two in PALB2 (c.509_510delGA and c.172_175delTTGT), one in NBN (c.657_661delACAAA) and one in RECQL (c.1667_1667 + 3delAGTA). To investigate the association of these alleles with DCIS risk, we used mutation frequencies in cancer-free controls as a reference (4000 to 4702 controls for different variants). To analyze survival, patients were followed on average for 156 months. Results A CHEK2 mutation (all variants combined) was associated with an increased risk of DCIS (OR = 1.7, p = 0.003). The risk was higher for CHEK2 truncating mutations (OR = 3.0, p = 0.001) than for a missense variant c.470T > C (OR = 1.5, p = 0.04). The risk was highest for carriers of CHEK2 truncating mutations with a family history of breast cancer (OR = 4.2, p = 0.01). There were no deaths reported in 52 CHEK2 mutation carriers during the follow up time. PALB2 , NBN and RECQL mutations were rare among cases and were not associated with DCIS risk in Polish women. Conclusions Based on the current study, women with a CHEK2 mutation face an increased risk of DCIS. The presence of DCIS should be considered during surveillance of CHEK2 mutation carriers. On the other hand, DCIS patients should receive genetic counseling and testing for CHEK2 mutations.